Typologia polskich partii politycznych według kryterium programowego - Kowalczyk, Krzysztof (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2014)
The author of the paper presents a typology of parliamentary parties in Poland on the basis of what he deems to be the key element when establishing a party, namely its political platform. He outlines social-democratic, liberal, Christian-democratic, conservative, people’s parties, independence parties and the parties he terms as non-standard ones. He concludes by presenting a table with an interesting list of all the parliamentary parties from the first to the seventh term.